Characteristics of participants in the first fully online National Diabetes Prevention Programme: A quantitative survey [version 4; peer review: 2 approved, 1 not approved] - Patricia M Kearney; Clair Haseldine; Gráinne O'Donoghue; Sheena M. McHugh; Liz Kirby; Margaret Humphreys; Fiona Riordan (HRB Open Research)
Background Diabetes prevention programmes (DPPs) are being implemented around the world to tackle the rise in type 2 diabetes. In 2021/22, the Health Service Executive(HSE) in Ireland piloted a fully online national diabetes prevention programme(NDPP). Characteristics and factors affecting participation may be different among people attending online DPPs compared to face-to-face programmes. The aim of this study was to describe the demographic, psychosocial and health characteristics of participants in the pilot of the online NDPP in Ireland. Methods A survey from the evaluation of the English NDPP was adapted for the Irish context with Patient and Public Involvement (PPI) input. The survey was sent (between April and June 2022) to all individuals who attended the initial assessment of the pilot NDPP (n=73). It contained questions on health status, co-morbidities, motivation to improve health, quality of life, self-efficacy, beliefs about the risk of diabetes, participation(e.g. recollection and understanding of invite, number of sessions attended), as well as demographic information. Results Response rate was 30.5% (n=22). Mean age of responders was 62 years (range 36–82 years) and over half were men (57.1%, n=12). The majority (81%, n=17) had attended 6 or more of the 14 sessions. Most (90.5% n=19) reported having family members or acquaintances with diabetes, had positive views of their current health status and high quality of life scores (71.4%, n= 15). Mental health scores were slightly higher than the national average. Over half (57.2%, n=12) were confident or very confident about participating in an online DPP. Almost all (95.2%, n=20) believed it was important to manage their risk of type 2 diabetes. Conclusions Participants in the online pilot NDPP had positive views of their general health and positive psychosocial characteristics affecting their decision to participate. These beliefs may be modifiable intervention targets to encourage participation among non-attenders in future programmes.